2017
DOI: 10.1039/c7cp02106b
|View full text |Cite
|
Sign up to set email alerts
|

The bouncing threshold in silica nanograin collisions

Abstract: Using molecular dynamics simulations, we study collisions between amorphous silica nanoparticles. Our silica model contains uncontaminated surfaces, that is, the effect of surface hydroxylation or of adsorbed water layers is excluded. For central collisions, we characterize the boundary between sticking and bouncing collisions as a function of impact velocity and particle size and quantify the coefficient of restitution. We show that the traditional Johnson-Kendall-Roberts (JKR) model provides a valid descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 57 publications
4
42
0
Order By: Relevance
“…At v = 150 m/s, strain is maximum in an oval region surrounding the contact plane; no sign of strain localization is observed that points at the occurrence of shear transformation zones that otherwise govern the plasticity of amorphous materials (Falk & Langer, 1998;Huang et al, 2013;Schuh & Lund, 2003). Since such shear transformation zones are actually observed in collisions of silica grains of comparable sizes (Nietiadi et al, 2017), we conclude that it is the softness of amorphous ice that precludes the existence of these zones in this material.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…At v = 150 m/s, strain is maximum in an oval region surrounding the contact plane; no sign of strain localization is observed that points at the occurrence of shear transformation zones that otherwise govern the plasticity of amorphous materials (Falk & Langer, 1998;Huang et al, 2013;Schuh & Lund, 2003). Since such shear transformation zones are actually observed in collisions of silica grains of comparable sizes (Nietiadi et al, 2017), we conclude that it is the softness of amorphous ice that precludes the existence of these zones in this material.…”
Section: Resultsmentioning
confidence: 73%
“…The value of the constant C depends strongly on the assumptions of energy dissipation during the collision and has been discussed to assume values between 0.3 and 57.9 (Krijt et al, ; Nietiadi et al, ). Even with the highest value of C , equation predicts bouncing to occur above v b =91 m/s.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach is non-trivial in the case of polar materials such as silica, where adsorbates may strongly influence interactions at the surface [14]. Thus, it has been found that when modeling silica collisions with clean surfaces, the colliding NPs stick rather than bounce over a wide range of velocities [15], in contrast to experiments [16][17][18]. One may presume [13] that the surface passivation by water-that is, the surface hydroxylationis responsible for this behavior.…”
Section: Introductionmentioning
confidence: 99%